The family welfare program handbook a guide for DOLE regional program implementors. (Labor Population Program Office, 1992)
"This handbook is primarily addressed to the Workers Amelioration and Welfare Division (WAWD), Chief and designated Population Program Coordinators (PPCs) so that they will be able to see more clearly the scope and nature of the tasks exported from them. It discusses the actual implementation of the In-Plant Family Welfare Program and convincing target clients (the grass-roots workers at the work place). It is also a reflection of the Labor Population Program Office's numerous dialogues and interactions with program implementors." It has 132 pages containing LPPD's programs, activities, services and future projects.